PERANCANGAN DAN PENGEMBANGAN PRODUK CNC MINI 2 AXIS DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Ahmad Anas Arifin; Kurnia Bekti Indarmawan; Desmas Arifianto Patriawan (POLITALA PRESS, 2022)
Mini lathe is often used for several consumers to simplify lathe work with small workpiece size. There are several sizes of mini lathe on the market, so, it needed several developments. Quality Function Development (QFD) is a developing method from a product or service. This method was used because this method was able to give approach value to develop machine design to meet consumer desires and needs. This study discussed the development of mini lathe based on customer needs which was obtained from questionnaire. The questionnaire was processed inti development data and the basic of comparison design concepts. There were two comparing design concepts, Assessment based on function, ergonomic, design for manufacture, and design for assembly index. Based on assessment, concept number 2 is chosen as best concept.